A low temperature resistant metal nanowire composite electrode sheet and preparation method thereof
By mixing metal nano wires with electrode active materials to melt, it melted it, forming a low -temperature metal nanivor composite electrode tablet, solving the problem of decline in the performance of lithium -ion batteries in low -temperature environments, and achieved higher ionic conductivity and Low temperature performance.
Patent Information
- Application Number
- CN202210284563.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-22
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-03-22
AI Technical Summary
Traditional lithium-ion batteries exhibit problems such as increased charge migration impedance and reduced diffusion rate in low temperature environments, resulting in a decline in battery performance.
Mixed metal nano wires and electrode active materials are mixed into slurry, coated on the streaming and heated to melt the metal nanivor wire, thereby forming a low -temperature metal nanivor composite electrode.
A significant reduction of the interface impedance of the battery under low temperature conditions, increasing the ion conductivity of LI+, and improving the low temperature performance of the lithium -ion battery.
Smart Images

Figure CN114628682B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a low-temperature resistant metal nanowire composite electrode sheet and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are the representative of modern high-performance batteries, and their main components include positive electrode materials, negative electrode materials, electrolytes, separators, binders, etc. Among them, binders are very important components of positive and negative electrode materials of lithium-ion batteries. They can tightly bind the active materials, conductive agents and current collectors in the electrode materials, enhance the electronic contact between the active materials and conductive agents or current collectors, and better stabilize the electrode structure.
[0003] Although traditional battery binders have good thermal stability and processing performance, when the ambient temperature is lower than the glass transition temperature of the binder, it will cause a large volume change, thus destroying the structure of the electrode. In addition, the binder is tightly coated on the surface of the active material and the conductive agent, making the Li + The inability to fully contact the active material results in a decrease in ionic conductivity. In addition, the charge migration impedance of lithium-ion batteries increases in low temperature environments, which reduces the diffusion rate of lithium ions in the electrode and also affects the low-temperature performance of lithium-ion batteries.
[0004] Nanowires, as a new type of material that can be industrially mass-produced and applied, have been applied in the field of lithium-ion batteries, such as Chinese patents CN113707862A, CN114122620A, etc. However, most of these technical solutions add nanowires as conductive additives to the battery in order to improve the electronic conduction of the electrode and thus improve the performance of the battery, and do not involve the low-temperature performance of the battery and its solution. The applicant's research found that metal nanowires still have high ionic conductivity under low temperature conditions. For example, the electrode slurry made by mixing silver nanowires with active substances has good low-temperature resistance. The ionic conductivity and electronic conductivity are both high under low temperature conditions, which can improve the low-temperature resistance of the battery. At present, the traditional coating process can be used to directly load the slurry containing metal nanowires onto the current collector, thereby significantly reducing the interfacial impedance and improving the Li + Transport conductivity, it is a good choice to replace traditional electrode binders. Summary of the invention
[0005] One of the purposes of the present invention is to provide a low-temperature resistant metal nanowire composite electrode sheet, which comprises metal nanowires, electrode active materials, and current collectors, wherein the metal nanowires wrap around the electrode active materials after melting and are jointly loaded onto the surface of the current collector.
[0006] Furthermore, the metal nanowire is selected from at least one of silver nanowire, tin nanowire, antimony nanowire and nickel nanowire.
[0007] Furthermore, the electrode active material is a common commercial electrode material on the market, including lithium vanadium phosphate material, lithium iron phosphate material, ternary positive electrode material, lithium manganese oxide material, etc. The electrode active material can be one or more of them.
[0008] Furthermore, the current collector is selected from at least one of aluminum foil and titanium foil.
[0009] Preferably, the following principles must be met when determining the metal nanowires and electrode active materials: the melting temperature of the metal nanowires is lower than the melting point of the current collector.
[0010] Furthermore, the mass ratio of the metal nanowires to the electrode active material in the composite electrode sheet is 1:4-100.
[0011] The second object of the present invention is to provide a method for preparing the above-mentioned low-temperature resistant metal nanowire composite electrode sheet, which comprises the following steps: (a) mixing metal nanowires with an organic solvent to form a slurry, and then adding an electrode active material to form an electrode slurry; (b) uniformly coating the electrode slurry prepared in step (a) on the surface of the current collector, and obtaining an electrode sheet after drying; (c) placing the electrode sheet prepared in step (b) in a protective atmosphere and heating it to melt the metal nanowires, and obtaining a low-temperature resistant metal nanowire composite electrode sheet after cooling.
[0012] Furthermore, the organic solvent in step (a) is selected from at least one of ethanol, ethylene glycol, propylene glycol, isopropanol, and N-methylpyrrolidone (NMP).
[0013] Furthermore, the metal nanowires in step (a) are in powder form, with a diameter within the range of 100-200 nm and an aspect ratio within the range of 100:1-50.
[0014] Furthermore, the solid-liquid ratio when preparing the slurry in step (a) is 0.1-0.5:1, and the solid-liquid ratio when preparing the electrode slurry is 0.1-0.5:1. The two slurries need to be stirred continuously during the preparation process, the stirring temperature is 20-60°C, and the total stirring time is 1-5h.
[0015] Furthermore, the drying temperature in step (b) is 80-110° C., the drying time is 1-5 hours, and the overall thickness of the electrode sheet obtained by drying is 20-300 μm.
[0016] Furthermore, the protective atmosphere in step (c) is selected from at least one of nitrogen, argon, helium and neon, the heating temperature is 200-500° C., and the insulation time at this temperature is 1-5 h.
[0017] The third object of the present invention is to provide a lithium-ion battery, the electrode of which adopts the above-mentioned low-temperature-resistant metal nanowire composite electrode sheet.
[0018] The present invention mixes metal nanowires, electrode active materials and alcohol solvents to form a slurry, which is then coated on a current collector to form an electrode sheet. Finally, the metal nanowires are heated to melt, thereby firmly combining the electrode active material and the current collector. The electrode sheet material provided by the present invention does not require a traditional binder, and the metal nanowires play a dual role of conductivity and bonding. The relevant principle is: a network of metal nanowires is melted and bonded to form an electrode sheet with excellent conductivity. In addition, heating causes the metal nanowires to melt and weld to each other, thereby achieving the purpose of bonding the active materials to form a current collector, thereby achieving the dual role of a conductive agent and a binder. Through the traditional coating process and the melting of metal nanowires, the electrode active material can be conveniently and efficiently firmly and evenly loaded onto the current collector. The present invention utilizes metal nanowires with superior ion conductivity to coat the electrode active material, which significantly reduces the interfacial impedance of the battery under low temperature conditions and improves Li + The ionic conductivity is improved, ultimately improving the low-temperature performance of lithium-ion batteries.
[0019] Compared with the prior art, the beneficial effects of the present invention are embodied in the following aspects: (1) the structure and composition of the existing lithium-ion battery electrode sheet are simplified, and the newly introduced metal nanowires replace the traditional battery binder, thereby solving the problem of battery performance degradation caused by changes in the physical and chemical properties of the electrode binder under low temperature conditions; (2) the button battery assembled with the electrode sheet prepared by the present invention as the positive electrode and the graphite negative electrode is tested for its low temperature performance at -20°C in an electrochemical workstation. The results show that its capacity is maintained at 121 mAh / g, verifying that the metal nanowire composite electrode sheet and the corresponding battery have good ion conductivity and low temperature performance; (3) The entire process flow is relatively simple and can be mass-produced on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1-4 They are SEM images of the surface morphology of the electrode sheet at different temperatures during the preparation of the silver nanowire composite graphene oxide lithium vanadium phosphate electrode sheet in Example 1.
[0021] Figure 5 This is the XPS photoelectron spectrum of the silver nanowire composite graphene oxide lithium vanadium phosphate electrode sheet prepared in Example 1.
[0022] Figure 6 This is a TEM image of the graphene oxide lithium vanadium phosphate electrode active material (precursor) in Example 1.
[0023] Figure 7This is a schematic diagram of the preparation process of the silver nanowire composite graphene oxide lithium vanadium phosphate electrode sheet in Example 1.
[0024] Figure 8 The specific capacity-voltage curve of a button-type full battery assembled using the silver nanowire composite graphene oxide lithium vanadium phosphate electrode sheet prepared in Example 1 and a graphite negative electrode.
[0025] Fig. 9 The specific capacity-coulombic efficiency-cycle curve of a button-type full battery assembled using the silver nanowire composite graphene oxide lithium vanadium phosphate electrode sheet prepared in Example 1 and a graphite negative electrode.
[0026] Fig.10 The current-voltage curve of a button-type full battery assembled using the silver nanowire composite graphene oxide lithium vanadium phosphate electrode sheet prepared in Example 1 and a graphite negative electrode.
[0027] Fig.11 The specific capacity-coulombic efficiency-cycle curve of a button-type full battery assembled with the silver nanowire composite graphene oxide lithium vanadium phosphate electrode sheet prepared in Example 1 and a graphite negative electrode at -20°C.
[0028] Fig.12 The specific capacity-coulombic efficiency-cycle curve of a button-type full battery assembled with the graphene oxide lithium vanadium phosphate electrode sheet prepared in Comparative Example 1 and a graphite negative electrode at -20°C. DETAILED DESCRIPTION
[0029] In order to enable ordinary technicians in the field to fully understand the technical solutions and beneficial effects of the present invention, further description is given below in conjunction with specific embodiments and drawings.
[0030] The metal nanowires and electrode active materials used in the present invention are purchased from Aladdin Co. The purity of various solvents used in the present invention is ≥ 99.9%. Other chemical reagents used in the present invention, unless otherwise specified, are obtained through conventional commercial channels.
[0031] Example 1
[0032] (1) 0.2 g of silver nanowire powder (diameter 100-200 nm, aspect ratio 100:1-50, the same below) was mixed with 2.5 mL (about 2.0 g) of anhydrous ethanol, stirred in a constant temperature stirrer at a speed of 2000 rpm and a temperature of 20°C for 1.5 h, and naturally cooled to room temperature to obtain a uniform mixed slurry; 1 g of the mixed slurry and 0.1 g of graphene oxide lithium vanadium phosphate active material were weighed and added into a 20 mL serum bottle successively, and stirred in a constant temperature stirrer at a speed of 2000 rpm and a temperature of 25°C for 1.5 h to obtain a uniform electrode slurry.
[0033] (2) The electrode slurry prepared in step (1) is loaded onto an aluminum foil using a 200 μm coater. After coating, the aluminum foil is placed in an oven and dried at 100° C. for 3 h to obtain a stable electrode sheet;
[0034] (3) placing the electrode sheet prepared in step (2) in a tubular furnace in a N2 atmosphere, heating the temperature to 300°C and keeping the temperature for 1.5 hours; during the heat preservation process, the silver nanowires melt and wrap the graphene oxide lithium vanadium phosphate electrode material to form a silver nanowire composite graphene oxide lithium vanadium phosphate electrode sheet.
[0035] Example 2
[0036] (1) 0.4 g of silver nanowire powder was mixed with 1.8 mL (about 2.0 g) of ethylene glycol, stirred in a thermostatic stirrer at a speed of 3000 rpm and a temperature of 30°C for 2.5 h, and naturally cooled to room temperature to obtain a uniform mixed slurry; 0.9 g of the mixed slurry and 0.1 g of lithium iron phosphate were weighed and added into a 20 mL serum bottle, and stirred in a thermostatic stirrer at a speed of 2000 rpm and a temperature of 35°C for 2.5 h to obtain a uniform electrode slurry.
[0037] (2) The electrode slurry prepared in step (1) is loaded onto an aluminum foil using a 150 μm coater. After coating, the aluminum foil is placed in an oven and dried at 100° C. for 3 h to obtain a stable electrode sheet;
[0038] (3) placing the electrode sheet obtained in step (2) in a tubular furnace in a N2 atmosphere, heating it to 300°C and keeping it warm for 2.5 hours; during the keeping warm process, the silver nanowires melt and wrap around the lithium iron phosphate to form a silver nanowire composite lithium iron phosphate electrode sheet.
[0039] Example 3
[0040] (1) 0.2 g of tin nanowire powder was mixed with 1.9 mL (about 2.0 g) of propylene glycol, stirred in a thermostatic stirrer at a speed of 2000 rpm and a temperature of 40°C for 3.5 h, and naturally cooled to room temperature to obtain a uniform mixed slurry; 0.8 g of the mixed slurry and 0.1 g of lithium iron phosphate were weighed and added into a 20 mL serum bottle, and stirred in a thermostatic stirrer at a speed of 2000 rpm and a temperature of 45°C for 3.5 h to obtain a uniform electrode slurry.
[0041] (2) The electrode slurry prepared in step (1) is loaded onto a titanium foil using a 200 μm coater. After coating, the titanium foil is placed in an oven and dried at 100° C. for 3 h to obtain a stable electrode sheet;
[0042] (3) placing the electrode sheet obtained in step (2) in a tubular furnace in an Ar atmosphere, heating the furnace to 300° C. and maintaining the temperature for 2.5 hours; during the temperature maintenance process, the tin nanowires melt and wrap around the lithium iron phosphate to form a tin nanowire composite lithium iron phosphate electrode sheet.
[0043] Example 4
[0044] (1) 0.4 g of tin nanowire powder was mixed with 2.5 mL (about 2.0 g) of isopropanol, stirred in a thermostatic stirrer at a speed of 3000 rpm and a temperature of 50°C for 4.5 h, and naturally cooled to room temperature to obtain a uniform mixed slurry; 0.7 g of the mixed slurry and 0.1 g of lithium vanadium phosphate were weighed and added into a 20 mL serum bottle, and stirred in a thermostatic stirrer at a speed of 2000 rpm and a temperature of 55°C for 4.5 h to obtain a uniform electrode slurry.
[0045] (2) The electrode slurry prepared in step (1) is loaded onto a titanium foil using a 150 μm coater. After coating, the titanium foil is placed in an oven and dried at 100° C. for 3 h to obtain a stable electrode sheet;
[0046] (3) placing the electrode sheet obtained in step (2) in a tubular furnace in an Ar atmosphere, heating the furnace to 300° C. and maintaining the temperature for 4.5 hours; during the heat preservation process, the tin nanowires melt and wrap around the lithium vanadium phosphate to form a tin nanowire composite lithium vanadium phosphate electrode sheet.
[0047] Example 5
[0048] (1) 0.2 g of antimony nanowire powder was mixed with 1.9 mL (about 2.0 g) of N-methylpyrrolidone, stirred in a thermostatic stirrer at a speed of 2000 rpm and a temperature of 20°C for 1.5 h, and naturally cooled to room temperature to obtain a uniform mixed slurry; 1.0 g of the mixed slurry and 0.2 g of lithium vanadium phosphate were weighed and added into a 20 mL serum bottle, and stirred in a thermostatic stirrer at a speed of 4000 rpm and a temperature of 25°C for 3.5 h to obtain a uniform electrode slurry.
[0049] (2) The electrode slurry prepared in step (1) is loaded onto an aluminum foil using a 200 μm coater. After coating, the aluminum foil is placed in an oven and dried at 100° C. for 3 h to obtain a stable electrode sheet;
[0050] (3) placing the electrode sheet obtained in step (2) in a tubular furnace with a He atmosphere, heating it to 400° C. and keeping it warm for 1.5 hours; during the keeping warm process, the antimony nanowires melt and wrap around the lithium vanadium phosphate to form an antimony nanowire composite lithium vanadium phosphate electrode sheet.
[0051] Example 6
[0052] (1) 0.4 g of antimony nanowire powder was mixed with 2.5 mL (about 2.0 g) of anhydrous ethanol, stirred in a thermostatic stirrer at a speed of 3000 rpm and a temperature of 30°C for 2.5 h, and naturally cooled to room temperature to obtain a uniform mixed slurry; 0.9 g of the mixed slurry and 0.3 g of lithium vanadium phosphate were weighed and added into a 20 mL serum bottle, and stirred in a thermostatic stirrer at a speed of 4000 rpm and a temperature of 35°C for 3.5 h to obtain a uniform electrode slurry.
[0053] (2) The electrode slurry prepared in step (1) is loaded onto an aluminum foil using a 150 μm coater. After coating, the aluminum foil is placed in an oven and dried at 100° C. for 3 h to obtain a stable electrode sheet;
[0054] (3) placing the electrode sheet obtained in step (2) in a tubular furnace in a He atmosphere, heating it to 400° C. and keeping it warm for 2.5 hours; during the keeping warm process, the antimony nanowires melt and wrap around the lithium vanadium phosphate, forming an antimony nanowire composite lithium vanadium phosphate electrode sheet.
[0055] Example 7
[0056] (1) 0.2 g of nickel nanowire powder was mixed with 1.8 mL (about 2.0 g) of ethylene glycol, stirred in a thermostatic stirrer at a speed of 2000 rpm and a temperature of 40°C for 3.5 h, and naturally cooled to room temperature to obtain a uniform mixed slurry; 1.0 g of the mixed slurry and 0.3 g of lithium vanadium phosphate were weighed and added into a 20 mL serum bottle, and stirred in a thermostatic stirrer at a speed of 4000 rpm and a temperature of 45°C for 3.5 h to obtain a uniform electrode slurry.
[0057] (2) The electrode slurry prepared in step (1) is loaded onto a titanium foil using a 200 μm coater. After coating, the titanium foil is placed in an oven and dried at 100° C. for 3 h to obtain a stable electrode sheet;
[0058] (3) placing the electrode sheet obtained in step (2) in a tubular furnace in a Ne atmosphere, heating it to 500° C. and keeping it warm for 3.5 hours; during the insulation process, the nickel nanowires melt and wrap around the lithium vanadium phosphate to form a nickel nanowire composite lithium vanadium phosphate electrode sheet.
[0059] Example 8
[0060] (1) 0.2 g of nickel nanowire powder was mixed with 1.9 mL (about 2.0 g) of propylene glycol, stirred in a thermostatic stirrer at a speed of 3000 rpm and a temperature of 50 ° C for 4.5 h, and naturally cooled to room temperature to obtain a uniform mixed slurry; 0.7 g of the mixed slurry and 0.3 g of lithium vanadium phosphate were weighed and added into a 20 mL serum bottle, and stirred in a thermostatic stirrer at a speed of 4000 rpm and a temperature of 55 ° C for 4.5 h to obtain a uniform electrode slurry.
[0061] (2) The electrode slurry prepared in step (1) is loaded onto a titanium foil using a 150 μm coater. After coating, the titanium foil is placed in an oven and dried at 100° C. for 3 h to obtain a stable electrode sheet;
[0062] (3) placing the electrode sheet obtained in step (2) in a tubular furnace in a Ne atmosphere, heating it to 500° C. and keeping it warm for 4.5 hours; during the insulation process, the nickel nanowires melt and wrap around the lithium vanadium phosphate to form a platinum nanowire composite lithium vanadium phosphate electrode sheet.
[0063] Example 9
[0064] (1) 0.4 g of silver nanowire powder was mixed with 2.5 mL (about 2.0 g) of anhydrous ethanol, stirred in a thermostatic stirrer at a speed of 3000 rpm and a temperature of 50°C for 3.5 h, and naturally cooled to room temperature to obtain a uniform mixed slurry; 1.0 g of the mixed slurry and 0.3 g of lithium iron phosphate were weighed and added into a 20 mL serum bottle, and stirred in a thermostatic stirrer at a speed of 4000 rpm and a temperature of 35°C for 3.5 h to obtain a uniform electrode slurry.
[0065] (2) The electrode slurry prepared in step (1) is loaded onto an aluminum foil using a 200 μm coater. After coating, the aluminum foil is placed in an oven and dried at 100° C. for 3 h to obtain a stable electrode sheet;
[0066] (3) placing the electrode sheet obtained in step (2) in a tubular furnace in an Ar atmosphere, heating the temperature to 400° C. and maintaining the temperature for 3.5 hours; during the heat preservation process, the silver nanowires melt and wrap around the lithium iron phosphate to form a silver nanowire composite lithium iron phosphate electrode sheet.
[0067] Example 10
[0068] (1) 0.2 g of nickel nanowire powder was mixed with 1.8 mL (about 2.0 g) of propylene glycol, stirred in a thermostatic stirrer at a speed of 2000 rpm and a temperature of 40°C for 3.5 h, and naturally cooled to room temperature to obtain a uniform mixed slurry; 0.8 g of the mixed slurry and 0.3 g of lithium iron phosphate were weighed and added into a 20 mL serum bottle, and stirred in a thermostatic stirrer at a speed of 4000 rpm and a temperature of 45°C for 3.5 h to obtain a uniform electrode slurry.
[0069] (2) The electrode slurry prepared in step (1) is loaded onto a titanium foil using a 200 μm coater. After coating, the titanium foil is placed in an oven and dried at 100° C. for 3 h to obtain a stable electrode sheet;
[0070] (3) placing the electrode sheet obtained in step (2) in a tubular furnace in an Ar atmosphere, heating it to 500° C. and keeping it warm for 3.5 hours; during the insulation process, the nickel nanowires melt and wrap around the lithium iron phosphate to form a nickel nanowire composite lithium iron phosphate electrode sheet.
[0071] In order to compare the electrochemical performance of the electrode sheet prepared by the method of the present invention with that of the electrode sheet prepared by the conventional method using a binder, we designed Comparative Example 1 for comparative test analysis.
[0072] Comparative Example 1
[0073] (1) 0.1 g of acetylene black, 0.1 g of polyvinylidene fluoride and 2.5 mL (about 2.0 g) of NMP were mixed, stirred in a thermostatic stirrer at a speed of 2000 rpm and a temperature of 20°C for 1.5 h, and naturally cooled to room temperature to obtain a uniform mixed slurry; 1.0 g of the mixed slurry and 0.1 g of graphene oxide lithium vanadium phosphate electrode active material were weighed and added into a 20 mL serum bottle in succession, and stirred in a thermostatic stirrer at a speed of 2000 rpm and a temperature of 25°C for 1.5 h to obtain a uniform electrode slurry.
[0074] (2) The electrode slurry prepared in step (1) is loaded onto an aluminum foil using a 200 μm coater. After coating, the aluminum foil is placed in an oven and dried at 100° C. for 3 h to obtain a stable graphene oxide lithium vanadium phosphate electrode sheet.
[0075] During the preparation of the silver nanowire composite graphene oxide lithium vanadium phosphate electrode sheet described in step (3) of Example 1, samples were taken at 20°C, 220°C, 240°C, and 260°C for SEM scanning, and the results were as follows: Figure 1-4 As shown in the figure, as the temperature rises, the silver nanowires gradually melt and cover the graphene oxide lithium vanadium phosphate material to achieve mutual compounding; at 260°C, the silver nanowires have basically been compounded on the graphene oxide lithium vanadium phosphate active material.
[0076] The silver nanowire composite graphene oxide lithium vanadium phosphate electrode sheet prepared in Example 1 was subjected to XPS testing, and the results are as follows: Figure 5 As shown in the figure, LVP@PrGO-Ag represents a silver nanowire composite graphene oxide lithium vanadium phosphate electrode sheet, and LVP@C represents a graphene lithium vanadium phosphate electrode sheet without composite silver nanowires. Figure 5 It can be seen that the silver nanowire composite graphene oxide lithium vanadium phosphate electrode has a 3d peak of the Ag element with a binding energy of 380eV, but the Ag peak does not appear in the original sample, which indicates that the silver nanowires have been successfully composited into the electrode.
[0077] The graphene oxide lithium vanadium phosphate electrode active material (precursor) in Example 1 was subjected to TEM test, and the results are as follows: Figure 6 As shown. Figure 6 It can be seen that the lithium vanadium phosphate particles in the graphene oxide lithium vanadium phosphate electrode active material (precursor) are evenly dispersed on the graphene sheet, and the particle size of the lithium vanadium phosphate material is about 10 nm.
[0078] In order to fully understand the performance of the electrode sheets prepared in each embodiment, the products of embodiment 1 and comparative example 1 were taken as examples, and assembled into batteries and analyzed and tested according to the following method: the prepared electrode sheets were punched into circular electrode sheets with a diameter of d = 10 mm, and then assembled into CR2032 button-type full batteries with graphite negative electrode sheets and Celgard 2500 lithium-ion battery separators under Ar atmosphere. The electrochemical performance at room temperature and -20°C was tested in an electrochemical workstation, and the relevant test results are shown in FIG. Figure 8-12 shown.
[0079] Figure 8 The specific capacity-voltage curves of the button-type full battery assembled with the silver nanowire composite graphene oxide lithium vanadium phosphate positive electrode sheet and the graphite negative electrode sheet prepared in Example 1 are in the voltage range of 2.7-4.3V at 1 cycle, 50 cycles, 100 cycles, 150 cycles, 200 cycles, and 300 cycles respectively. Figure 8 It can be seen that the voltage platform is stable during charge and discharge. After 300 cycles, the discharge specific capacity is 125.6mAh / g.
[0080] Fig. 9 The specific capacity-coulombic efficiency-cycle curve of the button-type full battery assembled with the silver nanowire composite graphene oxide lithium vanadium phosphate positive electrode sheet and the graphite negative electrode sheet prepared in Example 1, which was cycled 300 times at a 1C rate. Fig. 9 It can be seen that the first discharge specific capacity is 131.8 mAh / g, the coulombic efficiency has been stable at more than 99% since the 20th cycle, and the capacity retention rate is 80% after 300 cycles of charge and discharge.
[0081] Fig.10 The current-voltage curve of the first three cycles of the button-type full battery assembled with the silver nanowire composite graphene oxide lithium vanadium phosphate positive electrode sheet and the graphite negative electrode sheet prepared in Example 1 is shown in FIG. 1 , where LVP@Ag represents the silver nanowire composite graphene oxide lithium vanadium phosphate positive electrode sheet. Fig.10 It can be seen that there are redox peaks at 3.59V, 3.69V, and 4.07V during the reaction, proving that the reaction occurs completely and is reversible.
[0082] Fig.11 The button-type full battery assembled by using the silver nanowire composite graphene oxide lithium vanadium phosphate positive electrode sheet and the graphite negative electrode sheet prepared in Example 1 was first tested for its charge and discharge performance at different rates in a -20°C low temperature box, and then its electrochemical cycle stability was tested at the same rate to obtain a specific capacity-coulomb efficiency-cycle curve. Fig.11It can be seen that the first discharge specific capacity at -20°C is 128.8mAh / g; similar capacities can be achieved at different charging and discharging rates, proving that the battery reaction has good reversibility; and subsequently, under the same rate test, it can be seen that the coulombic efficiency of the battery reaction is stable at more than 99%.
[0083] Fig.12 The button-type full battery assembled by using the graphene oxide lithium vanadium phosphate positive electrode sheet and the graphite negative electrode sheet prepared in Comparative Example 1 was first tested for its charge and discharge performance at different rates in a -20°C low-temperature box, and then tested for its electrochemical cycle stability at the same rate. The specific capacity-coulomb efficiency-cycle curve diagram. Fig.12 It can be seen that the lithium vanadium phosphate positive electrode sheet prepared with traditional binder at -20°C has obvious capacity decay at different rates, and the charge and discharge specific capacity is very low, with poor low-temperature performance.
Claims
1. A method for preparing a low-temperature resistant metal nanowire composite electrode sheet, characterized in that: The composite electrode sheet comprises metal nanowires, an electrode active material, and a current collector, wherein the mass ratio of the metal nanowires to the electrode active material is 1:4-100, and the metal nanowires are melted to wrap around the electrode active material and are jointly loaded on the surface of the current collector; the metal nanowires are selected from at least one of powdered silver nanowires, tin nanowires, and antimony nanowires, and have a diameter of 100-200nm and an aspect ratio of 100:1-50; the electrode active material is selected from at least one of lithium vanadium phosphate material, lithium iron phosphate material, ternary positive electrode material, and lithium manganate material; the current collector is selected from at least one of aluminum foil and titanium foil, and the melting temperature of the metal nanowires is lower than the melting point of the current collector; The preparation method of the composite electrode sheet comprises: (a) mixing metal nanowires with an organic solvent to form a slurry, and then adding an electrode active material to form an electrode slurry; (b) uniformly coating the electrode slurry prepared in step (a) on the surface of the current collector, and obtaining an electrode sheet after drying; (c) placing the electrode sheet obtained in step (b) in a protective atmosphere and heating it to melt the metal nanowires, and cooling it to obtain a low-temperature resistant metal nanowire composite electrode sheet; the protective atmosphere is selected from at least one of nitrogen, argon, helium, and neon, the heating temperature is 200-400°C, and the insulation time at this temperature is 1-5h.
2. The preparation method according to claim 1, characterized in that: The organic solvent in step (a) is selected from at least one of ethanol, ethylene glycol, propylene glycol, isopropanol and NMP.
3. The preparation method according to claim 1, characterized in that: In step (a), the solid-liquid ratio of the metal nanowires and the organic solvent to prepare the slurry is 0.1-0.5:1, and the solid-liquid ratio of the electrode slurry is 0.1-0.5:1; the preparation process of both slurries requires stirring, the stirring temperature is 20-60°C, and the total stirring time is 1-5h.
4. The preparation method according to claim 1, characterized in that: The drying temperature in step (b) is 80-110° C., the drying time is 1-5 hours, and the thickness of the electrode sheet obtained by drying is 10-300 μm.
5. A lithium ion battery, characterized in that: The electrode of the lithium-ion battery adopts a low-temperature-resistant metal nanowire composite electrode sheet prepared by any one of the preparation methods in claims 1-4.
Citation Information
Patent Citations
Copper nanowire wound silicon-carbon composite material and preparation method and application thereof
CN113707862A
High-flame-retardant high-mechanical-strength high-adhesion lithium ion battery diaphragm and preparation method thereof
CN114122620A
Low-internal resistance lithium ion battery and preparation method thereof
CN104577117A
Aglomerated electroactive materials including Ag nanowire network and method for manufacturing the same
KR1020130055920A